HUBUNGAN KARAKTERISTIK IBU DENGAN KEJADIAN PRE-EKLAMSIA DI RSUI YAKSSI SRAGEN - Faizah Betty R; Yanti Akademi Kebidanan Estu Utomo Boyolali (Sekolah Tinggi Ilmu Kesehatan Estu Utomo Boyolali, 2011)
HUBUNGAN KARAKTERISTIK IBU DENGAN KEJADIAN PRE-EKLAMSIA DI RSUI YAKSSI SRAGEN Faizah Betty R & Yanti Akademi Kebidanan Estu Utomo Boyolali Abstrak Efforts to reduce morbidity and mortality due to pre-eclampsia can be achieved if prevention and early diagnosis of disease carried out as soon as possible. Early prevention efforts can be made if it can be identified major causative factors and incidence of risk factors pre-eclampsia. The purposes of this study are to determine the relationship characteristics included maternal age, parity and birth interval with the incidence of pre-eclampsia. This study is a retrospective case control approach is the case group with maternal pre-eclampsia while the control group was not with maternal pre-eclampsia, using total sampling technique. The subject of research a number of 175 cases of pre-eclampsia (as the case group) and 175 cases did not pre-eclampsia (as the control group). Univariate analysis, descriptively to describe the characteristics of the birth interval, the incidence of pre-eclampsia, age, and parity of mother; and multivariate analysis with logistic regression analysis with significance level of p <0.05 and OR value is taken from the b eksponent with 95 percent confidence interval. The results showed the relationship of labor interval, maternal age, and parity associated with the occurrence of pre-eclampsia. The longer the spacing of children (≥ 5 years), the greater risk of experiencing pre-eclampsia, the more maternal age (≥ 35 years) the greater risk of experiencing pre-eclampsia and primiparous mothers at greater risk of experiencing pre-eclampsia. Keywords: birth interval, maternal age, parity, incidence of pre-eclampsia.